Using Dramatic Arts to Enhance Empathic Communication Skills of Thai Medical Students - Pongpanich, Chanut (Journal of Fine and Applied Arts Khon Kaen University, 2025)
Empathic communication is a crucial skill for physicians, and dramatic arts have the potential to enhance it. However, there is limited research in Thailand on integrating such training into medical education. This study developed an 18-hour acting course for Thai medical students, based on Konstantin Stanislavski’s principles of creative state of mind, communion, and imagination, incorporating empathic communication training. The course was piloted with 6 medical students to refine the curriculum and then tested with 21 participants to assess its effectiveness. 19 participants communicated with simulated patients before and after the course to evaluate skill improvement. Mixed methods were employed to assess the course design. Over 90% of participants reported that acting techniques enhanced empathic communication and benefited their medical training. Participants showed increased communication skills across all areas, with notable improvements in empathy and body language. They noted that drama enhances both personal and interpersonal skills, with imagination being a key feature, making it a valuable tool for medical education and applicable to other healthcare professionals.